The genetic association of RUNX3 with ankylosing spondylitis can be explained by allele-specific effects on IRF4 recruitment that alter gene expression - Vecellio, M; Roberts, AR; Cohen, CJ; Cortes, A; Knight, JC; Bowness, P; Wordsworth, BP (BMJ Publishing Group, 2015)
Objectives To identify the functional basis for the genetic association of single nucleotide polymorphisms (SNP), upstream of the RUNX3 promoter, with ankylosing spondylitis (AS).